Fragments from a medieval archive: the life and death of Sir Robert Constable - McDonagh, Briony (Elsevier, 2013)
This article asks what we can know of historical individuals in pre-Reformation England. While recognizing the challenges of writing medieval biography, it points to the opportunities offered by a range of under-utilized sources for engaging both with medieval individuals and the pre-modern world more generally. Using the records of numerous property disputes and related cases litigated at the Westminster equity courts, it examines the actions and attitudes of one individual: Sir Robert Constable of Flamborough (c. 1478–1537), a Yorkshire landowner who was frequently brought before the courts for his involvement in local property disputes and ultimately implicated in the Pilgrimage of Grace. It explores Constable's activities through the multiple and often contradictory versions of events presented to the king, his advisors and the law courts, assessing his motivations and character while also recognizing that the fragmentary nature of the evidence means that Constable will always be an uncertain subject. In focussing on Constable and his connections to the lives and landscapes around him, the article also highlights much about the experiences and agency of the medieval men and women who shared his world. It considers the local personalities and community politics surrounding episodes of enclosure, building on recent work by social historians, archaeologists and historical geographers in order to draw attention to the roles played by ordinary and not-so-ordinary individuals in shaping the landscape. The paper not only underlines the importance of thinking geographically about the pre-modern world, but also goes some way towards ‘peopling’ the medieval countryside, conceptualizing it as a landscape brought into being through the attitudes and actions of those living and working within it.